Effects of Risk Analysis and Evaluation management Strategy on Organization’s Supply Chain Performance. - Mburu, David Kiarie; Ngugi, Dr. Patrick Karanja; Ogollah, Dr. Kennedy (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
Today’s market place is characterized by turbulence and uncertainty. Market turbulence hastended to increase in recent years for several reasons along the pply chain. Demand in almostevery industry sector seems to be more volatile. Product and technology life-cycles have shortened significantly and competitive product introduction make life cycle demand difficult to predict (WB, 2012). Considerable ‘chaos’ exists in supply chains through the effect of such actions as spromotion, quarterly sales incentives or decision rules such as quantities whichresults into continuous disruptions along the supply chain (Singhal & Hendricks, 2005).Today, vulnerability of Supply chains to disturbances or disruptions has increased and has received considerable attention by practitioners as well as academics (Skipper & Hanna, 2009). It’s not only the effect of external events such as natural disasters but also the impacts of changesin business trategy, the impact of one entity in the supply chain failing can as well lead to a number of entities closing down and in some instances the whole supply chain shuts down. The risk implications of the entwined global marketplace that characterize today’s supply chains have also been evidenced vividly in the recent global financial crisis. Many companies have experienced a change in their supply chain risk profile as a result of changes in their supply chain profile and changes in their business models. The doption of ‘lean’ practices, the move to outsourcing and a general tendency to reduce the size of the supplier base potentially increase supply chain vulnerability(Richard, 2008). The level of decision making along supply chain in manufacturing companies, quality of serviceand the type of relationship with other organizations erally influences the level of outputs expected from the functional and tertiary groups (Cooper & Ellram, 2003). The diversity and complexity of organizations, growth, strategic conceptualization & pursuit of adaptivemechanisms coupled with adverse changes in technology, and the global competitiveness of different markets, is beyond the efforts of an organization alone but between the supply chains (Cox & Watson, 2001). Most literature reveal that supply chain performance inturing companies is more appropriate as units of analysis than the entire organization management with the realization of the fact that those involved in the chain are in a position to lead in a number of possible directions (Miller & Ross, 2003).